2004
DOI: 10.1590/s1516-635x2004000400007
|View full text |Cite
|
Sign up to set email alerts
|

Performance of broilers fed diets containing natural growth promoters

Abstract: The present study evaluated the effect of different probiotics on the performance of broiler chickens. A thousand and fifty one-day-old male Cobb chicks were distributed in a completely randomized design in a 3 x 2 + 1 factorial arrangement (3 probiotics sources in the diet, 2 probiotics concentrations in drinking water and 1 control group), with 5 repetitions of 30 birds per parcel. The results showed better feed conversion (p<0.01) (1-21, 22-35 and 1-45 days) and weight gain (p<0.05) (22-35 and 1-45 days) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Feed intake (FI) and weight gain (WG) of the birds fed probiotics were similar to those of the NC birds in all rearing stages, except for those fed PR-III in the period of 1-40 days, which WG was lower than the NC birds (p<0.05) ( Table 2). Previous studies also found similar weight gain (Vargas et al, 2001;Lima et al, 2003;Pelicano et al, 2004) and feed intake (Pelicano et al, 2004;Flemming & Freitas, 2005) in birds supplemented or not with probiotics. According to Pelicano et al (2004), the similar or lower performance of birds fed probiotics as compared to negative control groups, may be due to an unbalance of the bird's gastrointestinal microflora consequent to the high number of microorganisms as compared to the quantities normally found in the digestive tract.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Feed intake (FI) and weight gain (WG) of the birds fed probiotics were similar to those of the NC birds in all rearing stages, except for those fed PR-III in the period of 1-40 days, which WG was lower than the NC birds (p<0.05) ( Table 2). Previous studies also found similar weight gain (Vargas et al, 2001;Lima et al, 2003;Pelicano et al, 2004) and feed intake (Pelicano et al, 2004;Flemming & Freitas, 2005) in birds supplemented or not with probiotics. According to Pelicano et al (2004), the similar or lower performance of birds fed probiotics as compared to negative control groups, may be due to an unbalance of the bird's gastrointestinal microflora consequent to the high number of microorganisms as compared to the quantities normally found in the digestive tract.…”
Section: Resultssupporting
confidence: 63%
“…The inclusion of probiotics in the diet has shown to produce contradictory results on broiler performance. Researchers have reported positive (Maiorka et al, 2001;Correa et al, 2003;Dematte Filho, 2004) none or negative effects (Vargas, 2001;Lima et al, 2003;Pelicano et al, 2004;Flemming & Freitas, 2005;Gunal et al, 2006) on broiler performance attributed to the action of probiotics. This variation in results was shown by Faria Filho et al (2006) in their literature review.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the total rearing period, from one to 42 days of age, none of the treatments statistically influenced the evaluated parameters, which was also observed by Lima et al (2003), who worked with Bacillus subtilis (1 × 10 10 CFU/g product), Pelicano et al (2004b), who used Bacillus subtilis, Bacillus licheniformis, Lactobacillus reuteri and Lactobacillus johnsonii, Appelt et al (2010), who tested different Bacillus subtilis feed inclusion levels, Boratto et al (2004), Junqueira et al (2006) and Silva et al, (2011). On the other hand, Santos et al (2004), including antibiotics and probiotics in broiler feeds, despite not detecting differences in body weight, weight gain or feed intake in broilers from one to 42 days of age, showed that the antibiotic product promoted better feed conversion ratio.…”
Section: Resultssupporting
confidence: 53%
“…The results of present study are in line with Habibi-Najafi et al 24 , who reported that dietary supplementation of prebiotic increased the WHC of meat. On the other hand, Pelicano et al 25…”
Section: Physico-biochemical Indicesmentioning
confidence: 98%
“…The results of present study are in line with Habibi-Najafi et al 24 , who reported that dietary supplementation of prebiotic increased the WHC of meat. On the other hand, Pelicano et al 25 reported that dietary inclusion of prebiotic has no significant effect on WHC of meat during storage condition. It is remarkable to note that water loss reduces meat nutritional value because some nutrients may be lost in exudate resulting in meat becoming less tender and bad in flavour.…”
Section: Physico-biochemical Indicesmentioning
confidence: 99%